An algebra problem by Jason Chrysoprase

Algebra Level 3

If 2 x = 3 y = 6 z 2^x = 3^y = 6^{-z} , where x , y , z x, y, z are all real non zero numbers, find 1 x + 1 y + 1 z \dfrac{1}{x} + \dfrac{1}{y} + \dfrac{1}{z} .


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Nov 10, 2016

2 x = 3 y = 6 z x log 2 = y log 3 = z log 6 = k \begin{aligned} 2^x = 3^y & = 6^{-z} \\ x\log 2 = y \log 3 & = -z \log 6 = k \end{aligned}

1 x + 1 y + 1 z = log 2 k + log 3 k log 6 k = log 6 k log 6 k = 0 \begin{aligned} \implies \frac 1x + \frac 1y + \frac 1z & = \frac {\log 2}k + \frac {\log 3}k - \frac {\log 6}k \\ & = \frac {\log 6}k - \frac {\log 6}k \\ & = \boxed{0} \end{aligned}

Jason Chrysoprase
Nov 10, 2016

Let 2 x = 3 y = 6 z = k 2^x = 3^y = 6^{-z} = k , so k 1 x = 2 , k 1 y = 3 , k 1 z = 6 k^{\frac{1}{x}} = 2, k^{\frac{1}{y}} = 3, k^{\frac{1}{-z}} = 6

Note that 2 × 3 = 6 2 \times 3 = 6 , so

k 1 x × k 1 y = k 1 z k 1 x + 1 y = k 1 z 1 x + 1 y = 1 z \begin{aligned} k^{\large \frac{1}{x}} \times k^{\large \frac{1}{y}} &= k^{\large \frac{1}{-z}} \\ k^{\large \frac{1}{x} + \frac{1}{y}} &= k^{\large \frac{1}{-z}} \\ \dfrac{1}{x} + \dfrac{1}{y} &= \dfrac{1}{-z} \end{aligned}

Thus,

1 x + 1 y + 1 z = 1 z + 1 z = 0 \dfrac{1}{x} + \dfrac{1}{y} + \dfrac{1}{z} = \dfrac{1}{-z} + \dfrac{1}{z} = 0

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...